Faradaic processes beyond Nernst’s law: density functional theory assisted modelling of partial electron delocalisation and pseudocapacitance in graphene oxides - Li, Junfu; O'Shea, James N.; Hou, Xianghui; Chen, George Z. (Royal Society of Chemistry, 2017)
The study of electron delocalisation in oxygen atom segregated zones in graphene, aided by the first-principles density functional theory, has revealed extra energy bands of ≥ 2 eV wide around the Fermi level, predicting faradaic charge storage occurring in a wide range of potentials, which disagrees with Nernst’s Law but accounts well for the so called pseudocapacitance of heteroatommodified graphene based electrode materials in supercapacitors.